2006
DOI: 10.1364/ol.31.002553
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared supercontinuum generation to 45 μm in ZBLAN fluoride fibers by nanosecond diode pumping

Abstract: A mid-infrared supercontinuum (SC) is generated in ZBLAN (ZrF4-BaF2-LaF3-AlF3-NaF...) fluoride fibers from amplified nanosecond laser diode pulses with a continuous spectrum from approximately 0.8 microm to beyond 4.5 microm. The SC has an average power of approximately 23 mW, a pump-to-SC power conversion efficiency exceeding 50%, and a spectral power density of approximately -20 dBm/nm over a large fraction of the spectrum. The SC generation is initiated by the breakup of nanosecond laser diode pulses into f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
123
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(125 citation statements)
references
References 10 publications
(9 reference statements)
0
123
0
2
Order By: Relevance
“…Due to the properties of silica glass, SC generation has been limited to visible and near infrared wavelengths. Today, with the development of soft glass microstructured optical fibers [9], the effective nonlinear coefficient of fibers can be enhanced by a few orders of magnitudes [10], the group velocity dispersion of the fiber can be tailored to a variety of profiles [9] and the range of operating wavelength can also be extended into mid-infrared [11,12]. The use of such fibers promises SC applications in the mid-IR such as mid-IR Light Detection and Ranging (LIDAR) [3], mid-IR optical coherence tomography (OCT) [4], mid-IR absorption spectroscopy [5] and mid-IR coherent anti-Stokes Raman scattering (CARS) [6,7,8], etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the properties of silica glass, SC generation has been limited to visible and near infrared wavelengths. Today, with the development of soft glass microstructured optical fibers [9], the effective nonlinear coefficient of fibers can be enhanced by a few orders of magnitudes [10], the group velocity dispersion of the fiber can be tailored to a variety of profiles [9] and the range of operating wavelength can also be extended into mid-infrared [11,12]. The use of such fibers promises SC applications in the mid-IR such as mid-IR Light Detection and Ranging (LIDAR) [3], mid-IR optical coherence tomography (OCT) [4], mid-IR absorption spectroscopy [5] and mid-IR coherent anti-Stokes Raman scattering (CARS) [6,7,8], etc.…”
Section: Introductionmentioning
confidence: 99%
“…A Mid-IR SC source would also be a good substitute for current mid-IR sources such as optical parametric oscillators and quantum cascade lasers. Some studies on soft-glass fiber based mid-IR SC generation have demonstrated that they can generate SC up to 4∼5µm [11,12,13]. However, to the best of our knowledge, these mid-IR SC studies have been more focused on generating bandwidth extending into the mid-IR rather than the coherence of the generated SC.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, fluoride glasses have extremely low water content and provide low absorption over the entire transparency window from the deep ultraviolet (200 nm) to the mid-infrared (8 μm), making it ideal for the generation of multi-octave-wide supercontinua. Previous work on supercontinuum generation in ZBLAN fluoride glass has however focused on step-index fibres in the spectral range from the visible to the mid-IR [4][5][6], except for a recently published paper [7] in which SC spectra down to a record 200 nm in the deep-UV was generated inside a solid-core photonic crystal fibre (PCF). In both tellurite and ZBLAN PCFs, the dispersion can be tailored with proper fibre design.…”
mentioning
confidence: 99%
“…These applications place widely varying demands on the characteristics of a supercontinuum source. Novel optical fibers can yield supercontinua spanning the ultraviolet into the midinfrared [6][7][8]. However, a requirement for shot-to-shot repeatability and a smooth spectrum limits the allowable propagation length, restricting the bandwidth [7].…”
mentioning
confidence: 99%